Experimental Investigation of Composite Material in Boat Hull. Issue 1 (December 2020) - Ashokkumar, S; Antony Casmir Jayaseelan, G; Akash, A; Bharathi Raja, V; Abeesh, A
Abstract: Natural composite materials have been used in many fields of our lives to save the environment. Especially, Teak sawdust and wood ash due to its environmental sustainability, mechanical properties, and recyclability have been utilized as many applications like to make boat hull in marine engineering the main objectives of this paper are teak sawdust, wood ash, and sisal fiber are used to make the composite material. This experimental focus on the change in mechanical properties of wood ash, sisal fiber with epoxy resin matrix with different volume ratios of teak sawdust reinforcement fabricated by using the hand layup method. For this purpose, a composite material with various weight percentages such as 10% of teak sawdust (R1) and 20% of teak sawdust (R2) reinforcements have been developed with 150 and 300 microns particle size and its compare with the mechanical properties of the Impact resistance test, hardness test as well as mainly to compare the water absorption test properties of composite materials has to be analyzed in detail.